Cultural imprinting: Ancient origins of entrepreneurship and innovation in Germany - Michael Fritsch; Fabian Wahl; Michael Wyrwich (Friedrich Schiller University Jena, 2021)
A region's present-day economic performance can be deeply anchored in historical factors. We provide the first systematic evidence of a deep imprinting effect in the context of Roman rule in the south-western part of Germany nearly 2,000 years ago. Our analysis reveals that regions in the former Roman part of Germany show a stronger entrepreneurship and innovation culture today, evident by higher levels of quantity and quality entrepreneurship and innovation. The data indicate that this lasting "Roman effect" was constituted by the early establishment of interregional social and economic exchange and related infrastructure. Our findings thus help in unpacking the hidden cultural roots of present-day economic performance, with important implications for research and economic policy.
Keywords: N9; O1; I31; 330; Entrepreneurship; innovation; historical roots; Romans; Limes